2017
DOI: 10.1051/matecconf/201710301023
|View full text |Cite
|
Sign up to set email alerts
|

Chloride Resistance Behavior on Nano-Metaclayed Ultra-High Performance Concrete

Abstract: Abstract. Nowadays, the application of nano materials is getting attention to enhance the conventional concrete properties. The ultrafine particles of nano material also will help reducing the formation of micro pores by acting as a filler agent, produce a very dense concrete and will reduce the growth of micro pores in the UHPC structures. The introduction of nano materials in concrete is to increase the strength and durability of concrete. One of the most important factor affecting concrete durability is chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Lu et al [ 20 ] used iron tailing powder and studied the mechanical performance and the microstructure under different curing conditions; they concluded that the steam curing regime was the most effective at early ages, while the warm-water curing had the best effect at late ages. Some authors also recommend the inclusion of nanoparticles (e.g., nanosilica, nano metaclay or calcium nanocarbonate) to enhance performance [ 21 , 22 , 23 , 24 , 25 ] or ground glass to lower costs [ 26 , 27 , 28 ]. These nanoparticles improve concrete properties due to their chemical reactivity and their physical effect (filler and nucleation effects).…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al [ 20 ] used iron tailing powder and studied the mechanical performance and the microstructure under different curing conditions; they concluded that the steam curing regime was the most effective at early ages, while the warm-water curing had the best effect at late ages. Some authors also recommend the inclusion of nanoparticles (e.g., nanosilica, nano metaclay or calcium nanocarbonate) to enhance performance [ 21 , 22 , 23 , 24 , 25 ] or ground glass to lower costs [ 26 , 27 , 28 ]. These nanoparticles improve concrete properties due to their chemical reactivity and their physical effect (filler and nucleation effects).…”
Section: Introductionmentioning
confidence: 99%